HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN DI DESA MINGGIR KECAMATAN WINONGAN KABUPATEN PASURUAN - Silvi Wulandari; Nurun Ayati Khasanah; Fitria Edni Wari (MEDICA MAJAPAHIT, 2025)
Stunting is a nutritional problem throughout the world, including Indonesia. SSGI results in 2021 the prevalence rate of stunting in Indonesia reaches 24.4% with Pasuruan district 18.10% in 2021 and 13.4% in 2022. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-59 months in Mingir Village. This type of research uses analytic observational with a cross sectional design. Sampling was determined by simple random sampling of 315 respondents. Retrieval of data from secondary data. Bivariate analysis using the Chi-Square test. The results of the chi- square test showed that there was a significant relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-59 months in Minggir Village (p=0.000<0.05) with OR=0.045<1 test results, meaning that toddlers who are exclusively breastfed are a factor protective against stunting by 0.045 times. Exclusive breastfeeding can reduce the incidence of stunting. Therefore, health workers need to promote exclusive breastfeeding and recommend giving additional food in the form of animal protein.